Alternative funding sources for University of the Philippines Diliman Libraries - Coballes, Brian Aljer B. (2006)
Academic libraries face economic crisis. High cost of maintenance and other operating expenses and the great need to modernize libraries challenge head librarians of the academic libraries of the University of the Philippines, Diliman Campus.